Progressive Insurance : paying a lawyer to defend your sister's killer - Heatherman, Ryan; Swanepoel, Ilze; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Progressive Insurance faced a widespread public relations crisis when Matt Fisher took to his personal Tumblr site to post a scathing account of his family's experience with the company who insured his deceased sister. The blog entry went "viral" overnight, panning Progressive's use of their attorney to seemingly assist in the defense of the driver who collided into his sister's automobile, taking her life. This case examines the moral, economic, and legal views of business decision-making, as well as the social media consequences of a perceived imbalance between the three approaches. The question for Progressive Insurance is how to best mitigate the negative consequences of the current social media crisis and to avoid any recurrence.
Originally published in Heatherman, R., Swanepoel, I., & ORourke, J. S. (2013). Progressive Insurance: Paying a lawyer to defend your sisters killer.13-05. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Progressive Insurance; Corporate image; Insurance companies -- Public relations